Response of tropical peat swamp forest tree species seedlings to macro nutrients - Tri Wira Yuwati; Dony Rachmanadi; Purwanto Santoso (Center for Journal Management and Publication, 2015)
AbstractEfforts of restoration of degraded tropical peat swamp forest were facing constraints due to the low available nutrient level of peat. The transplanted peat swamp forest species seedlings experienced low survival rate and poor growth performance. This study aimed to demonstrate the response of ten tropical peat swamp forest species seedlings whether climax and pioneer species to macro-nutrients addition in the nursery. The growth performance of climax and pioneer tropical peat swamp species seedlings was recorded following addition of macro nutrients of Nitrogen (N), Phosphorus(P), Potassium(K) and Dolomitic limestone (CaMg). The result showed that Alstonia spatulata and Parartocarpus venenosus showed positive growth response following macro nutrients addition. This study concluded that tropical peat swamp pioneer species has lower necessity for macro-nutrients addition than tropical peat swamp climax species.